170 Uncontrolled Diabetes Mellitus is associated with Complications of Peyronie's Disease. Issue 1 (1st April 2022) - Karakus, S.; Burnett, A.L.; Joseph, C.; Dai, X.; Hawksworth, D.
ABSTRACT: Introduction: Peyronie's disease (PD) is a connective tissue disorder of the penis characterized by an abnormality in the collagen structure of the penile tunica albuginea resulting in plaque formation and penile deformity. The prevalence of PD is estimated to be 3.2-8.9% overall and as high as 20.3% in men with diabetes mellitus (DM). However, the impact of the severity of DM on PD complications is unclear. Objective: We aimed to investigate the association between uncontrolled DM and PD complications. Methods: We performed a retrospective study of patients with PD and DM presenting to our institution between December 2015 and June 2020. Clinical history, PD complications, erectile status, and clinical parameters of DM were analyzed. Penile deformities were determined by physical exam, photographs, and penile Doppler ultrasound. HbA1c level greater than 7% at the time indicated uncontrolled DM. Results: A total of 119 patients were evaluated. HbA1C levels were documented in 68 patients (median level of 7.2%). Thirty-six patients (36/68, 52.9%) had an HbA1c level >7% (uncontrolled DM). Data collection parameters have been shown in Table 1. Regression analysis indicated a significant association between the degree of penile curvature and status of uncontrolled DM after adjustment for age, body mass index, presence of hypertension, hyperlipidemia, and cardiovascular disease, and smoking status (B=13 degrees, 95% CI=1-25 degrees, p=0.04). An increase in HbA1c level after the initial diagnosis of PD positively correlated with a formation of penile plaque (rho=0.34, p=0.04). Conclusions: Our study suggested that uncontrolled DM and a further increase in HbA1c levels after the PD diagnosis significantly impact the severity of PD. Revealing mechanisms behind this will help us develop better management strategies in diabetic PD patients. Disclosure: No